2017
DOI: 10.14348/molcells.2017.0073
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Based Approach Reveals Differential Regulation of Visceral Adipose Tissue Proteins between Metabolically Healthy and Unhealthy Obese Patients

Abstract: Obesity and the metabolic disorders that constitute metabolic syndrome are a primary cause of morbidity and mortality in the world. Nonetheless, the changes in the proteins and the underlying molecular pathways involved in the relevant pathogenesis are poorly understood.In this study a proteomic analysis of the visceral adipose tissue isolated from metabolically healthy and unhealthy obese patients was used to identify presence of altered pathway(s) leading to metabolic dysfunction. Samples were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Engelmann et al experimentally induced thyrotoxicosis in healthy volunteers to explore the effects of l -thyroxine excess on the plasma proteome with a main focus on coagulation markers [ 11 ]. Therefore, the aim of our study was to evaluate changes in the plasma proteome in patients with hypothyroidism after replacement treatment with appropriate doses of l -thyroxine using the 2D-DIGE mass spectrometry approach [ 12 ]. Exploring the plasma proteome changes upon the transition from a hypothyroid to euthyroid state will help in understanding the thyroxine-mediated changes taking place in circulating proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Engelmann et al experimentally induced thyrotoxicosis in healthy volunteers to explore the effects of l -thyroxine excess on the plasma proteome with a main focus on coagulation markers [ 11 ]. Therefore, the aim of our study was to evaluate changes in the plasma proteome in patients with hypothyroidism after replacement treatment with appropriate doses of l -thyroxine using the 2D-DIGE mass spectrometry approach [ 12 ]. Exploring the plasma proteome changes upon the transition from a hypothyroid to euthyroid state will help in understanding the thyroxine-mediated changes taking place in circulating proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several adipokines, cytokines, metabolites, and microRNAs are implicated in obesityinduced diseases, some are dysregulated in more than one disease while some show potential as disease-specific biomarkers. Their expression levels can identify individuals with or at risk of developing obesity-related diseases such as inflammatory diseases 8 , diabetes 9 , CVDs 10 and metabolically unhealthy obese people 11 .…”
Section: Maldi-ms Matrix Assistant Laser Desorption/ionization Mass Smentioning
confidence: 99%
“…Proteomics has been especially helpful in biomarker discovery for chronic diseases, not limited to cancer 12 , and obesity 11,13 . Proteomics provides a platform to study the entire proteome in a given sample, and allows for qualitative and quantitative protein profile that can discriminate between healthy and diseased samples 14 .…”
Section: Maldi-ms Matrix Assistant Laser Desorption/ionization Mass Smentioning
confidence: 99%
“…Several reports on expression proteomics have shown that differential protein expression profiles exist in relation to different metabolic states [5,6,7]. In one study, a proteomic analysis of visceral fat tissue from obese people with and without metabolic syndrome (MetS) revealed that individuals characterized as MHO had an increased abundance of proteins related to adipose tissue expansion and antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, a proteomic analysis of visceral fat tissue from obese people with and without metabolic syndrome (MetS) revealed that individuals characterized as MHO had an increased abundance of proteins related to adipose tissue expansion and antioxidant capacity. In comparison, the MUHO group showed increased abundance of proteins that related to mitochondrial and the lipid droplet metabolic activities [6]. In another study, 20 proteins were reported to be differentially expressed between MHO and MUHO individuals and most of these proteins were related to inflammatory and lipid processes [5].…”
Section: Introductionmentioning
confidence: 99%